Penerapan Metode Steepest Ascent Hill Climb pada Permainan Puzzle - Hairul Anam; Feby Sabilhul Hanafi; Ahmad Fauzal Adifia; Ahmad Firdaus Ababil; Saiful Bukhori (INFORMAL: Informatics Journal, 2018)
Puzzle is one example of the application of artificial intelligence, in the process of completion there are many search algorithms that can be applied. The 8 puzzle solution will be faster obtained if the array principle is used with a variation of the Steepest-Ascent Hill Climbing (Hill Climbing algorithm by choosing the sharpest / steepest slope) with the correct heuristic parameters and distance heuristics and combined with LogList as the storage state ever passed to overcome the problems in the hill climbing algorithm itself and avoid the looping state that has been passed. Steepest Ascent Hill Climbing is an algorithm method that is widely used for optimization problems. The application of the SAHC (Steepest Ascent Hill Climbing) Algorithm to the puzzle is needed so that the game is completed with optimal time.